Financiamento do BNDES para obras e serviços de empresas Brasileiras no exterior - Fernanda Lira Goes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– From 2002 to 2016 National Bank of Economic and Social Development (BNDES, in Portuguese) financed a total amount of US 14 billion for 14 engineering Brazilian companies. Exporting construction services was executed in 11 countries located in Central America, South America and Africa, Angola itself received around US 4 billion, meanwhile Odebrecht concentrated almost 80% of the total financed amount.
Keywords: H2; 330; BNDES financing; Angola; Odebrecht; Brazil